Is it possible for sustainability? The case from the new capital city of Indonesia - Agustino, Leo; Hikmawan, M. Dian; Silas, Jonah (Frontiers in Political Science, 2024)
The decision to relocate the nation's capital from Jakarta is not without reason. Jakarta, the nation's capital, is regarded as less than ideal, with numerous issues such as flooding, air pollution, poor water quality, and political and environmental sustainability. This research will be based on the framework of ecological citizenship to investigate active citizens. The lesson from other countries that relocate their capital city as a comparison. This research uses a qualitative research method with a literature study type of research. reviewing several previous studies on citizenship and academic texts on moving the nation's capital, studies on moving the capital, and legislation on the nation's capital. This research tries to explore how the government gives much attention to social exclusion and inclusion. Ecological concerns have not been on the agenda of public discussion. Only a few local activists are active in mining cases in East Kalimantan who care about it. However, this research provides more information on the ecological citizenship community of Indonesia's new capital city in the context of the sustainability agenda.